Flame-retardant composite yarn for extreme service environments and method of making same

CN123027675APending Publication Date: 2026-11-03DEZHOU HUANYUAN ECOLOGICAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611020270.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

现有包芯纱技术中,纤维组分界面结合力不足,阻燃材料在洗涤或摩擦过程中容易脱落,导致防火阻燃性能下降,难以满足极端服役环境的需求。

Method used

Using basalt filaments as the core and pre-oxidized fibers as the flame-retardant coating, the fiber structure is modified with an interface compatibilizer, and an antistatic agent, a cohesive agent and water are used to form a transition interface film to enhance the adhesion between fibers. The silicone oil agent is combined to enhance the interfacial force, forming a dense composite yarn structure.

Benefits of technology

It improves the flame retardancy and overall performance of composite yarn, enhances the abrasion resistance and bending resistance of yarn, reduces the peeling of the coating layer, and meets the service requirements of extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of textiles, and particularly discloses a flame-retardant composite yarn for extreme service environments and a preparation method thereof; the flame-retardant composite yarn for extreme service environments comprises a core body and a flame-retardant coating layer, the core body is a 200D basalt filament, the flame-retardant coating layer is a pre-oxidized fiber, the pre-oxidized fiber is modified by an interfacial compatibilizer, and the raw materials of the interfacial compatibilizer include an antistatic agent, a cohesive agent and water; the application uses the pre-oxidized fiber as the flame-retardant coating layer and the basalt filament as the core body to improve the overall tensile strength and the flame-retardant performance of the composite yarn, avoids yarn fracture failure under high temperature, and better adapts to extreme complex environments; the antistatic agent, the cohesive agent and water are used as the interfacial compatibilizer to provide the skin-core interfacial shear strength of the composite yarn and reduce the peeling phenomenon of the coating layer under the working conditions of stretching, bending and friction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the textile field, and in particular to a flame-retardant composite yarn for extreme service environments and its preparation method. Background Technology

[0002] In the textile materials field, with the continuous development of industry, the demand for high-performance fiber materials capable of withstanding extreme service environments is increasing. Especially in hazardous scenarios such as high temperatures and flammability, including industries like firefighting, aerospace, and metallurgy, materials with good flame-retardant properties are needed to ensure the safety of personnel and equipment. To meet the demands of extreme service environments, core-spun yarn technology is considered an effective method to achieve both strength and flame retardancy.

[0003] Existing core-spun yarn technology mostly uses conventional fibers such as polyester, cotton, and nylon as the sheath. The interfacial bonding between different fiber components is insufficient, and the adhesion between the sheath fibers and the core yarn directly affects the covering effect and the overall performance of the yarn. Other methods involve attaching flame-retardant materials to the fiber surface through spraying, coating, or impregnation. However, due to the limited adhesion between the flame-retardant materials and the fibers, the flame-retardant layer is easily detached during washing or friction, leading to a decrease in fire-retardant performance. Summary of the Invention

[0004] To address the shortcomings of existing flame-retardant composite yarns, this application provides a flame-retardant composite yarn for extreme service environments and its preparation method.

[0005] Firstly, this application provides a flame-retardant composite yarn for extreme service environments, employing the following technical solution: A flame-retardant composite yarn for extreme service environments includes a core and a flame-retardant coating layer. The core is a 200D basalt filament, and the flame-retardant coating layer is a pre-oxidized fiber. The pre-oxidized fiber is modified with an interface compatibilizer, the raw materials of which include an antistatic agent, a cohesive agent, and water.

[0006] By adopting the above technical solutions, basalt filaments possess high strength, high temperature resistance, and aging resistance, enabling them to withstand the overall tensile force and abrasion load of the composite yarn. As the core of the yarn's stress, they prevent yarn breakage and failure at high temperatures, support the outer coating layer, and prevent the yarn from collapsing and disintegrating after the pre-oxidized fibers carbonize, thus better adapting to extreme and complex environments. The pre-oxidized fibers, acting as a flame-retardant coating layer, quickly form a dense char layer upon contact with fire, isolating oxygen and heat from inward conduction, protecting the internal basalt core from direct impact by high-temperature heat flow, and improving the flame-retardant effect of the composite yarn. Simultaneously, the pre-oxidized fibers, being organic flexible fibers, compensate for the brittleness and easy breakage caused by friction of basalt, improving the yarn's softness, bending resistance, and abrasion resistance.

[0007] Antistatic agents, cohesive agents, and water are used as interface compatibilizers to synergistically modify the surface of pre-oxidized fibers, forming an over-bonding layer between the pre-oxidized fibers and basalt filaments. This provides shear strength at the core-sheath interface of the composite yarn and reduces the phenomenon of coating peeling under tensile, bending, and friction conditions.

[0008] Preferably, the mass ratio of the antistatic agent, the coagulant, and the water is (0.3-0.8):(1-3):10.

[0009] Preferably, the binding agent is a silicone oil.

[0010] By adopting the above technical solution, the silicone oil agent can rely on its own low surface energy flexible segments to wet the surface of the pre-oxidized fiber, and rely on van der Waals forces and hydrogen bonds to adsorb on the active sites of hydroxyl and carboxyl groups generated after the oxidation of the pre-oxidized fiber, thus wrapping the surface of the pre-oxidized fiber monofilament and improving the cohesion of the pre-oxidized fiber itself.

[0011] Meanwhile, the siloxane segments can adhere to the smooth and inert surface of basalt filaments. The silicon element forms intermolecular forces with the silicon-oxygen skeleton on the basalt surface, creating a flexible transition interface film between the pre-oxidized filament and the inorganic basalt. This enhances the overall density of the composite yarn and reduces the phenomenon of coating slippage and delamination.

[0012] Dispersed silicone oil molecules cross-link with each other, forming a continuous, thin and flexible silicone film on the fiber surface, reducing friction and wear between monofilaments and improving the overall wear resistance and repeated bending resistance of the coating layer; it will not block the fiber pores and affect the air permeability and carbonization, and has excellent interfacial adhesion, enhancing the bonding and locking between the pre-oxidized fiber coating layer and the basalt core.

[0013] Preferably, the silicone oil agent is modified, including the following specific steps: Octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide were mixed and subjected to a first heating reaction under nitrogen protection to obtain pre-modified silicone oil. The pre-modified silicone oil was then mixed with 2-chloroethoxyethanol and a solvent, refluxed, and subjected to a second heating reaction. After the reaction, the solvent was removed by vacuum distillation to obtain the modified silicone oil agent.

[0014] By adopting the above technical solution, tetramethylammonium hydroxide catalyzes the ring-opening polymerization of octamethylcyclotetrasiloxane to generate linear polydimethylsiloxane long chains, which enhances the high-temperature stability of silicone oil agents. By using 1,3-bis(aminopropyl)tetramethyldisiloxane for end capping, active amino groups can be introduced at both ends of the siloxane molecular chain. The amino groups can form hydrogen bonds with carboxyl and hydroxyl groups, and at the same time, the amino groups can combine with hydroxyl groups on the surface of basalt filaments, thereby enhancing the bonding force between the core and the flame-retardant coating layer.

[0015] The amino-modified polysiloxane is then reacted with 2-chloroethoxyethanol to graft ethoxy ether segments onto the amino sites, which promotes the uniform dispersion of the silicone oil agent in the aqueous system, enables it to be miscible and compatible with the antistatic agent, and promotes the uniform adhesion of the antistatic agent to the surface of the silicone film. This avoids the accumulation of static electricity caused by the silicone oil insulation, and promotes the composite yarn to have both good static electricity and bonding effects.

[0016] Preferably, the first heating reaction is at 80-145°C and the second heating reaction is at 80-90°C.

[0017] Preferably, the mass ratio of the octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide is 20:(1-3):(0.1-0.3), and the mass ratio of the pre-modified silicone oil, 2-chloroethoxyethanol, and solvent is 10:(0.3-0.8):(10-15).

[0018] Preferably, the antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate.

[0019] Secondly, this application provides a method for preparing flame-retardant composite yarn for extreme service environments, employing the following technical solution: A method for preparing flame-retardant composite yarn for extreme service environments includes the following specific steps: First, pre-oxidized fiber, antistatic agent, cohesive agent and water are mixed and soaked to obtain pre-oxidized fiber. The pre-oxidized fiber is then carded, drawn and spun to obtain pre-oxidized yarn, which is then wrapped on the surface of 200D basalt filament and subjected to gradient hot pressing to form a flame-retardant composite.

[0020] By adopting the above technical solution, through the synergistic effect of each component, the pre-oxidized fiber precisely wraps the core yarn, and the internal stress is released through gradient heat setting. This enables the composite yarn to have no exposed core, no broken yarn, uniform yarn, and a dense and stable structure, which can meet the long-term service requirements under harsh working conditions such as extreme high temperature, high load and strong corrosion.

[0021] Preferably, the mass ratio of pre-oxidized yarn to basalt filament is 10:(15-20).

[0022] In summary, this application has the following beneficial effects: 1. Because this application uses basalt filaments as the core, it bears the overall tensile force and abrasion load of the composite yarn, serving as the core of the yarn's stress, preventing yarn breakage and failure at high temperatures, supporting the outer coating layer, and preventing the yarn from collapsing and disintegrating after the pre-oxidized fibers carbonize, thus better adapting to extreme and complex environments. The pre-oxidized fibers, as a flame-retardant coating layer, quickly form a dense char layer upon contact with fire, improving the flame-retardant effect of the composite yarn. Antistatic agents, cohesive agents, and water are used as interface compatibilizers to synergistically modify the surface of the pre-oxidized fibers, providing shear strength at the core-sheath interface of the composite yarn and reducing the phenomenon of coating layer peeling under tensile, bending, and friction conditions.

[0023] 2. In this application, silicone oil is used as a binding agent. The silicon element of the siloxane chain segment forms intermolecular forces with the silicon-oxygen skeleton on the basalt surface. It is adsorbed on the active sites of hydroxyl and carboxyl groups generated after the pre-oxidized filament is oxidized by van der Waals forces and hydrogen bonds, and is wrapped on the surface of the pre-oxidized filament monofilament. A flexible transition interface film is built between the pre-oxidized filament and the inorganic basalt, which enhances the overall density of the composite yarn and reduces the phenomenon of coating layer slippage and delamination. Detailed Implementation

[0024] The present application will be further described in detail below with reference to the embodiments.

[0025] All raw materials used in the examples are commercially available. Example Example 1

[0026] This embodiment provides a flame-retardant composite yarn for extreme service environments, comprising a core and a flame-retardant coating layer. The core is 200D basalt filament, and the flame-retardant coating layer is pre-oxidized fiber. The pre-oxidized fiber is modified with an interface compatibilizer, the raw materials of which include an antistatic agent, a cohesive agent, and water. The mass ratio of pre-oxidized fiber to basalt filament is 10:18. The pre-oxidized fiber has a breaking strength of 1.88 cN / dtex, a fineness deviation rate of 6%, a length deviation rate of 2%, and an elongation of 23%. The mass ratio of antistatic agent, cohesive agent, and water is 0.5:2:10. The antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, and the cohesive agent is octamethylcyclotetrasiloxane.

[0027] A method for preparing flame-retardant composite yarn for extreme service environments includes the following specific steps: First, pre-oxidized fiber, antistatic agent, cohesive agent and water are mixed and soaked for 2 hours. The pre-oxidized fiber is then removed and dried to obtain the treated pre-oxidized fiber. The pre-oxidized fiber is then carded, drawn and spun to obtain pre-oxidized yarn. Then, a wrapping machine is used to wrap the pre-oxidized yarn around the surface of 200D basalt filament. The mass ratio of pre-oxidized yarn to basalt filament is 10:18. The single wrap twist is designed to be 200T / m. Gradual gradient hot pressing and shaping is carried out at 140-150-160℃, with a roller pressing of 0.25MPa, to form a 6.7Nm / D flame-retardant composite yarn.

[0028] Example 2

[0029] The difference between Example 2 and Example 1 is that the mass ratio of antistatic agent, coagulant and water is 0.3:3:10.

[0030] Example 3 The difference between Example 3 and Example 1 is that the mass ratio of antistatic agent, coagulant and water is 0.8:1:10.

[0031] Example 4 The difference between Example 4 and Example 1 is that the mass ratio of pre-oxidized yarn to basalt filament is 10:15.

[0032] Example 5 The difference between Example 5 and Example 1 is that the mass ratio of pre-oxidized yarn to basalt filament is 10:20.

[0033] Example 6 The difference between Example 6 and Example 1 is that the silicone oil agent has been modified.

[0034] A method for preparing flame-retardant composite yarn for extreme service environments includes the following specific steps: S1: Octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide are mixed and reacted under nitrogen protection at 80°C for 2 hours, followed by a reaction at 145°C for 2 hours to obtain pre-modified silicone oil. The mass ratio of octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide is 20:2:0.2. The pre-modified silicone oil is mixed with 2-chloroethoxyethanol and tetrahydrofuran solvent, refluxed, and reacted under 80°C for 6 hours. After the reaction, the solvent is removed by vacuum distillation to obtain modified silicone oil. The mass ratio of the pre-modified silicone oil, 2-chloroethoxyethanol, and solvent is 10:0.5:13.

[0035] S2: First, mix and soak the pre-oxidized fiber, antistatic agent, cohesive agent and water for 2 hours. Take out the pre-oxidized fiber and dry it to obtain the treated pre-oxidized fiber. Then, process the pre-oxidized fiber into carding, drawing and spinning to obtain pre-oxidized yarn. Then, use a wrapping machine to wrap the pre-oxidized yarn onto the surface of 200D basalt filament. The mass ratio of pre-oxidized yarn to basalt filament is 10:18. The single wrap twist is designed to be 200T / m. Gradually heat-press and shape it at 140-150-160℃, roll press 0.25MPa to form a 6.7Nm / D flame-retardant composite yarn.

[0036] Example 7 The difference between Example 7 and Example 6 is that the mass ratio of octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide is 20:1:0.3.

[0037] Example 8 The difference between Example 8 and Example 6 is that the mass ratio of octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide is 20:3:0.1.

[0038] Example 9 The difference between Example 9 and Example 6 is that the mass ratio of pre-modified silicone oil, 2-chloroethoxyethanol, and solvent is 10:0.3:15.

[0039] Example 10 The difference between Example 10 and Example 6 is that the mass ratio of pre-modified silicone oil, 2-chloroethoxyethanol, and solvent is 10:0.8:10.

[0040] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no inclusion agent is used in the interface compatibilizer raw material.

[0041] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no interface compatibilizer is used in the interface compatibilizer raw material.

[0042] Performance testing The flame-retardant composite yarns for extreme service environments provided in Examples 1-10 and Comparative Examples 1-2 of this application were subjected to the following performance tests, and the specific test results are shown in Table 1.

[0043] Detection methods I. Fracture Strength The tensile breaking strength of the flame-retardant composite yarn prepared in this application was tested in accordance with GB / T3916-2013 "Determination of breaking strength and elongation at break of single yarn in packaged textiles (CRE method)".

[0044] II. Flame retardant properties The flame retardant properties of the flame-retardant composite yarn prepared in this application were tested in accordance with GB / T 5455-2014 "Determination of vertical damage length, smoldering and afterflame time of textiles".

[0045] III. Spinability Test Referring to the standard FZ / T 01086-2020 "Textile Yarn Hairiness Determination Method - Projection Counting Method", the total number of hairs with a protrusion length ≥2mm on one side of the yarn per unit length is used to determine the hairiness index of the flame-retardant composite yarn prepared in this application. At the same time, a yarn length measuring machine is used to take 3 strands from each bobbin, with a total length of 150m per strand. The yarn tension is (1.2±0.2)cN / tex. A magnifying glass is used to distinguish the core exposure of the composite yarn prepared in this application, and the core exposure rate is determined.

[0046] Table 1: Performance Test Results Data Table

[0047] The performance test results show that the composite yarn prepared in this application uses pre-oxidized fiber to coat basalt filaments, which improves the overall yarn strength while maintaining good flame retardant properties. A comparison of Comparative Examples 1-2 with Example 1 shows that changing the flame retardant properties of the interfacial compatibilizer in Comparative Examples 1-2 affects the overall performance of the prepared composite yarn, as indicated by the performance test results. This further illustrates that the conventional method of directly coating basalt filaments with pre-oxidized fiber results in poor compatibility, leading to coating layer detachment and peeling, thus affecting the overall performance of the composite yarn.

[0048] As can be seen from Examples 6-10, by modifying the silicone oil agent, the performance test results show that the overall performance of the prepared composite yarn is improved. This further illustrates that by incorporating amino and ethoxy ether segments on the surface of the silicone oil agent, the bonding force between the core and the flame-retardant coating layer is strengthened, thereby improving the flame-retardant effect, heat resistance and strength of the composite yarn.

[0049] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A flame-retardant composite yarn designed for extreme service environments, characterized in that, It includes a core and a flame-retardant coating layer. The core is 200D basalt filament, and the flame-retardant coating layer is pre-oxidized fiber. The pre-oxidized fiber is modified with an interface compatibilizer, and the interface compatibilizer raw materials include antistatic agent, cohesive agent and water.

2. The flame-retardant composite yarn for extreme service environments according to claim 1, characterized in that, The mass ratio of the antistatic agent, the coagulant, and the water is (0.3-0.8):(1-3):

10.

3. The flame-retardant composite yarn for extreme service environments according to claim 2, characterized in that, The binding agent is a silicone oil agent.

4. The flame-retardant composite yarn for extreme service environments according to claim 3, characterized in that, The silicone oil agent has been modified, including the following specific steps: Octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide were mixed and subjected to a first heating reaction under nitrogen protection to obtain pre-modified silicone oil. The pre-modified silicone oil was then mixed with 2-chloroethoxyethanol and a solvent, refluxed, and subjected to a second heating reaction. After the reaction, the solvent was removed by vacuum distillation to obtain the modified silicone oil agent.

5. The flame-retardant composite yarn for extreme service environments according to claim 4, characterized in that, The first heating reaction is at 80-145℃, and the second heating reaction is at 80-90℃.

6. The flame-retardant composite yarn for extreme service environments according to claim 4, characterized in that, The mass ratio of the octamethylcyclotetrasiloxane, 1,3-bis(aminopropane)tetramethyldisiloxane, and tetramethylammonium hydroxide is 20:(1-3):(0.1-0.3), and the mass ratio of the pre-modified silicone oil, 2-chloroethoxyethanol, and solvent is 10:(0.3-0.8):(10-15).

7. The flame-retardant composite yarn for extreme service environments according to claim 1, characterized in that, The antistatic agent is octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate.

8. A method for preparing flame-retardant composite yarn for extreme service environments as described in any one of claims 1-7, characterized in that, The specific steps include the following: First, pre-oxidized fiber, antistatic agent, cohesive agent and water are mixed and soaked to obtain pre-oxidized fiber. The pre-oxidized fiber is then carded, drawn and spun to obtain pre-oxidized yarn, which is then wrapped on the surface of 200D basalt filament and subjected to gradient hot pressing to form flame-retardant composite yarn.

9. The method for preparing flame-retardant composite yarn for extreme service environments according to claim 8, characterized in that, The mass ratio of pre-oxidized yarn to basalt filament is 10:(15-20).